FASILITASI PENGEMBANGAN “KAMPUNG PENG-ANGGURAN” KAMPUNG KB MELATI KELURAHAN BLOTONGAN - Carolina Day; Daru Purnomo; Dwi Andriani; Uray Noor Ramada; Fickny Djody Turangan; Novia Widyastuti (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The community service activity of the students of Faculty of Communication and Social Sciences of Satya Wacana Christian University was done at the Village of ‘Family Planning’ Melati (Kampung Keluarga Berencana ‘KB’ Melati), this community service activity was supported by Women Empowerment, Child’s Protection, Population Control, and Family Planning Office (DP3APPKB) of Salatiga City. The community service is aimed to rebrand and to promote the Village and to increase the agriculture potencies of Kampung KB Melati. One of the programs which was already planned by the people and agencies related to the village is the thematic village where the people of Kampung KB Melati are going to plant and cultivate grapes in their graveyard this program is called Kampung Peng-Angguran (The Grape Village). Started from identifying the problems, making programs, and the implementation of the programs, the students were working to involve the people of the village. The programs that were planned by the students to support the Kampung Peng-Angguran programs were such as workshop to educate the people on how to plant the grape and the students also helped to facilitate to get the assistances from the government especially the Farming and Food Agency of Salatiga City.